Comparison of C2HEST and MC2HEST Scores as Predictors of New-Onset Atrial Fibrillation in Patients with Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention at Haji Adam Malik Hospital Medan - Hanifah, Putri Vidya; Nasution , Ali Nafiah; Putra , Hilfan Ade (CoinReads Media Prima, 2025)
Introduction: To evaluate whether the C2HEST and mC2HEST scores have good ability as predictors of new-onset atrial fibrillation in patients with acute coronary syndrome undergoing percutaneous coronary intervention at HAM Hospital Medan. Method: This study is a retrospective cohort study. Retrospective data were collected by total sampling from all medical records of ACS patients at Adam Malik Hospital from January to September 2024. Prospective data were collected consecutively until the minimum sample size was met. Samples included in the research analysis were those that met the inclusion criteria without exclusion criteria. Results: As a predictive method, the mC2HEST score is as good as the C2HEST score, with AUCs of 0.713 and 0.728, respectively. The cut-off point obtained is the same for both scores, which is >3. The C2HEST score has a sensitivity of 73.7%, specificity of 52.6%, while the mC2HEST score has a sensitivity of 78.9%, specificity of 55.1%. The total number of samples that met the criteria was 108 patients. Patients with new-onset atrial fibrillation numbered 19 (17.6%). The youngest patient was 30 years old and the oldest was 81 years old. The average age in patients with new-onset atrial fibrillation was 67 years and without new-onset atrial fibrillation was 57 years. This study also yielded a new scoring system as an alternative predictive method. Conclusion: The mC2HEST score is as good as the C2HEST score as a predictor of new-onset atrial fibrillation in patients with acute coronary syndrome undergoing percutaneous coronary intervention at HAM Hospital Medan.